2001
DOI: 10.1038/89782
|View full text |Cite
|
Sign up to set email alerts
|

TACI-ligand interactions are required for T cell activation and collagen-induced arthritis in mice

Abstract: Interactions of the tumor necrosis factor superfamily members B lymphocyte stimulator (BLyS) and a proliferation-inducing ligand (APRIL) with their receptors-transmembrane activator and CAML interactor (TACI) and B cell maturation molecule (BCMA)-on B cells play an important role in the humoral immune response. Whereas BCMA is restricted to B cells, TACI is also expressed on activated T cells; we show here that TACI-Fc blocks the activation of T cells in vitro and inhibits antigen-specific T cell activation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
107
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(114 citation statements)
references
References 31 publications
4
107
0
2
Order By: Relevance
“…Assays were performed by a previously reported method [21]. Briefly, antigen-induced T cell adhesion was quantified by using a colorimetric assay described for measuring intracellular succinate dehydrogenase content with MTT [3(4,5-dimethyl-thiazol-2-yl)-2,5-diphenyl tetrazolium bromide] [22].…”
Section: Methodsmentioning
confidence: 99%
“…Assays were performed by a previously reported method [21]. Briefly, antigen-induced T cell adhesion was quantified by using a colorimetric assay described for measuring intracellular succinate dehydrogenase content with MTT [3(4,5-dimethyl-thiazol-2-yl)-2,5-diphenyl tetrazolium bromide] [22].…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that BLyS plays roles in the process of inflammation-associated lymphoproliferation and GC formation in the rheumatoid synovitis [22]. Serum BLyS levels were also reportedly elevated in collagen-induced arthritis (CIA) mouse model and AA rat model [29,33], with BLyS antagonism TACI-Ig having both preventive and therapeutic effects [37,38]. Zhang et al previously reported that elevated serum level of BLyS is closely correlated with profoundly increased anti-collagen type II autoantibody production in CIA mice [33].…”
Section: Discussionmentioning
confidence: 96%
“…(6,22) In an RA model of mice, TACI-Fc also reduces the tissue damage and prevents the progression of the disease. (23) A MAb, Lymphostat-B (Human Genome Sciences, Inc.), against human BLyS protein is being tested in a clinical trial for SLE.…”
Section: Discussionmentioning
confidence: 99%